Montezuma Quail in the Edwards Plateau of Texas: Detection, Occurrence, and Habitat - Zachary J Pearson; Eric D Grahmann; Fidel Hernández; Robert Perez; Leonard A Brennan; Humberto L Perotto-Baldivieso (National Quail Symposium Proceedings, 2022)
Montezuma quail (Cyrtonyx montezumae) were historically found throughout nearly every county in the Edwards Plateau region of Texas, USA. Over the last century, shifting land use, reduction of fire on the landscape, and the subsequent encroachment of woody vegetation have constricted the distribution of Montezuma quail to a few counties in the southern portion of the Edwards Plateau. A renewed interest in management for Montezuma quail over the last decade has been met with a lack of information regarding their habitat requirements in this region. This lack of general information and increased sightings of this elusive species in areas where Ashe’s juniper (Juniperus ashei) had been removed led to the initiation of this study to identify detection and site use. During April–August of 2015 and 2016, biweekly call-back surveys were conducted at 60 randomly stratified locations distributed across 9 properties in Edwards and Kinney counties, Texas. During each survey, weather conditions were recorded. Additionally, vegetation at each of the 60 survey locations was quantified. Montezuma quail were detected at 46% (28 of 60) of the survey locations during 6.7% of the total site visits during 2015 and 2016. Detection of Montezuma quail during call-back surveys was mostly explained by temperature. When temperatures exceeded 25 °C, probability of detection dropped below 70%. Site use by Montezuma quail was best explained by bunchgrass density as probability of site use exceeded 50% when bunchgrass density exceeded 0.63 plant/m2. Future researchers may be more successful searching for Montezuma quail with an understanding of the environmental conditions under which they are most detectable. Furthermore, since relatively dense stands of bunchgrass were associated with site occupancy, this metric gives managers a management target to shoot for when restoring Montezuma quail habitat in the region.
Keywords: Montezuma quail; Cyrtonyx montezumae; Mearns quail; Edwards Plateau